A triple stimulus responsive double-layer hydrogel actuator and preparation method thereof

By introducing the oxide nano nano belt in the hydraulic agglomerator to form a double layer of hydrogel forcer, the existing hydraulic gel force force can only respond to the stimulus of a single environment, and realize it. For the response to temperature, pH, and near -infrared light, it has good mechanical performance and self -healing performance.

CN114854046BActive Publication Date: 2025-01-24NANJING FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210495989.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-09
Publication Date
2025-01-24
Estimated Expiration
2042-05-09

AI Technical Summary

Technical Problem

Existing hydrogel actuators can only respond to a single environmental stimulus and are difficult to meet multiple response needs.

Method used

By introducing the oxide nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nanotranscele band to form a double layer of hydrogel, the thermal response of poly N-isopropyl acrylamide, the pH response and the pH of polyacrylic acid, and The light and thermal conversion of gallery nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nanotraach response to temperature, pH, and near -infrared light stimulation.

Benefits of technology

It achieves rapid response to triple environmental stimuli of temperature, pH and near-infrared light, has good mechanical properties and self-healing properties, and is suitable for underwater robots, grippers, valve switches and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114854046B_ABST
    Figure CN114854046B_ABST
Patent Text Reader

Abstract

The present invention discloses a triple stimulus responsive double-layer hydrogel actuator and a preparation method thereof. The two-layer hydrogel network is composed of a combination of a polyacrylic acid-polyacrylamide hydrogel and a poly (N-isopropylacrylamide-carboxymethylcellulose) hydrogel, respectively. The poly (acrylic acid-polyacrylamide) layer hydrogel is polymerized by a lignin-potassium persulfate-metal ion initiation system, and graphene oxide nanoribbons are added thereto to improve its mechanical properties, self-healing ability and electrical conductivity, while providing the double-layer hydrogel with photothermal conversion capability. The poly (N-isopropylacrylamide-carboxymethylcellulose) layer is polymerized by light initiation to provide the double-layer hydrogel with temperature response and pH response capabilities. Based on the above characteristics, the double-layer hydrogel actuator has the performance of triple stimulus response to temperature, pH and near-infrared light, and has potential applications in the fields of soft robots and valve switches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of intelligent driving materials, and in particular to a triple stimulus responsive double-layer hydrogel actuator and a preparation method thereof. Background Art

[0002] Hydrogel is a water-rich polymer gel with a three-dimensional network structure. At present, hydrogels have been widely used in food preservation, biomedicine, tissue engineering and other fields. Hydrogel actuators are devices composed of hydrogels that can respond to specific environments. Environmental stimulus-responsive hydrogel actuators composed of multiple polymers have shown great application potential in fields such as soft robots, drug delivery, and smart sensors. The power of this responsive actuator usually comes from the heterogeneous structure of two layers of hydrogel. Under different conditions, the difference in swelling and swelling produced by the heterogeneous structure drives it to perform movements such as bending. However, the hydrogel actuators usually prepared are mainly composed of an active layer and an inert layer, that is, the active layer receives and responds to environmental stimulus signals to shrink or swell. The inert layer does not have the ability to respond, and forms a heterogeneous structure with the active layer to play a supporting role, so that the contraction movement of the active layer hydrogel evolves into the bending movement of the double-layer heterogeneous hydrogel. The problem with this double-layer hydrogel is that it can only respond to one layer of the active layer hydrogel, and the actuation conditions are relatively simple. Therefore, it is still challenging to construct multi-responsive hydrogels.

[0003] Poly(N-isopropylacrylamide) is a widely used thermoresponsive polymer, which contains both hydrophilic amide groups and hydrophobic isopropyl groups in its molecular chain. When the external temperature is higher than the lower critical solution temperature of poly(N-isopropylacrylamide) (≈32°C), the hydrophilic effect of the amide group dominates, and the hydrogen bonding between the amide group and the water molecules causes the hydrogel to absorb a large amount of water, causing the hydrogel to swell. When the external temperature is higher than its lower critical solution temperature, the hydrophobic effect of the isopropyl group dominates, the water inside the hydrogel is discharged, and the hydrogel shrinks.

[0004] Polyacrylic acid is a common synthetic polymer hydrogel. Its molecular chain contains a large number of carboxyl groups, which makes it easy to carry out structural design and chemical modification to make the hydrogel material more functional. It is widely used in the fields of drug controlled release, separation and extraction, sensors and bionics. In an acidic environment, the protonation of the carboxyl groups in polyacrylic acid causes the hydrogel network to shrink and some water is discharged, that is, polyacrylic acid has a certain pH responsiveness.

[0005] The gel initiation system composed of calcium lignin sulfonate-persulfate-metal ions has the characteristics of being able to initiate polymerization reactions stably, quickly and evenly, and can initiate polymerization reactions without adding accelerators or heating the hydrogel system. In addition, the phenolic hydroxyl groups on calcium lignin sulfonate can form hydrogen bonds with the carboxyl groups of polyacrylic acid, and metal ions can also form coordination bonds with the carboxyl groups. These bonds and interactions will give the hydrogel good mechanical properties and self-healing properties.

[0006] Graphene oxide nanoribbons are prepared from multi-walled carbon nanotubes through a simple oxidation process and have a ribbon structure. Graphene oxide nanoribbons continue the good physical and chemical properties of carbon nanomaterials, such as chemical stability, electrical conductivity and photothermal conversion performance. Compared with graphene and carbon nanotubes, the extremely high aspect ratio and unique edge effect of graphene oxide nanoribbons make it more flexible and adjustable. In the field of smart hydrogels, the addition of graphene oxide nanoribbons can not only improve the mechanical properties of hydrogels, but also combine with thermoresponsive hydrogels to make them have the ability to respond to near-infrared light. Summary of the invention

[0007] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a triple-responsive hydrogel actuator and a preparation method thereof, which can respond to the triple stimulation of temperature, pH and near-infrared light, and meet the use requirements of underwater robots, grippers, valve switches, etc. Another technical problem to be solved by the present invention is to provide an application of the above triple-responsive hydrogel actuator.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0009] Multi-walled carbon nanotubes are oxidized and peeled into graphene oxide nanoribbons by a simple oxidation process, and then added into the network of polyacrylic acid-polyacrylamide to improve the mechanical properties, self-healing properties and strain sensing properties of the hydrogel. The above-mentioned polyacrylic acid-polyacrylamide hydrogel is used as the first layer, and the poly N-isopropylacrylamide-carboxymethylcellulose hydrogel with added graphene oxide nanoribbons is used as the second layer to obtain a double-layer hydrogel actuator. The two layers of hydrogel produce volume contraction or expansion under different conditions, that is, the two layers of hydrogel are active layers and inert layers under different conditions. Based on the properties of the above-mentioned hydrogel, the double-layer hydrogel actuator can respond to three environmental conditions: temperature, pH and near-infrared light, and can achieve reversible bending at a large angle of almost 360°. In addition, the polyacrylic acid hydrogel layer shows strong self-healing properties and strain sensing properties. Therefore, the triple-responsive double-layer hydrogel can be used in underwater robots, grippers, valve switches and other fields.

[0010] The preparation method of the triple-responsive hydrogel actuator comprises the following steps:

[0011] 1) Disperse a certain amount of multi-walled carbon nanotubes in concentrated sulfuric acid, slowly add potassium permanganate, stir evenly under magnetic stirring, raise the system to a certain temperature and continue stirring. Add ice water containing hydrogen peroxide to end the reaction. After standing, separate the product, and then wash it several times with deionized water, hydrochloric acid solution, ethanol and ether in turn to obtain graphene oxide nanoribbons;

[0012] 2) Add different amounts of acrylic acid and acrylamide monomers, dispersant, pre-initiator system and graphene oxide nanoribbons prepared in step 1) into a beaker and stir evenly with water. Add metal ion solution under ice water bath conditions, stir vigorously for a short time and pour into the mold for polymerization, and control the thickness of this layer of hydrogel;

[0013] 3) Place N-isopropylacrylamide, crosslinker, graphene oxide nanoribbons, and carboxymethyl cellulose in deionized water and stir, add a certain amount of photoinitiator and stir for a certain period of time in an ice water bath. Pour the obtained pre-gel solution on the polyacrylic acid-polyacrylamide layer prepared in step 2), place it for a period of time, and then perform photoinitiated polymerization under ultraviolet light to obtain a double-layer hydrogel;

[0014] 4) The double-layer hydrogel is cut into strips, and the strip hydrogel bends toward the layer containing poly (N-isopropylacrylamide) under near-infrared light or in a hot water environment. When the bent strip hydrogel is placed in an acidic solution, the double-layer hydrogel bends toward the layer containing polyacrylic acid.

[0015] The method for preparing the triple-responsive hydrogel actuator is characterized by:

[0016] In step 1), the mass of the multi-walled carbon nanotubes is 0.5-1.5 g, the volume of concentrated sulfuric acid is 150-250 mL, the mass of potassium permanganate is 2-3 g, the mixed solution is heated to 50-65° C., the concentration of hydrogen peroxide ice water is 5-20%, and the concentration of hydrochloric acid solution is 10-30%.

[0017] In step 2), the dispersants used include polyvinyl pyrrolidone and sodium lauryl sulfate, and the initiator system is calcium lignin sulfonate-potassium persulfate-metal ions, wherein the metal ions include iron ions and silver ions.

[0018] In step 2), the mass fraction of graphene oxide nanoribbons is 0.1-0.5%, the mass fraction of acrylic acid and acrylamide monomers is 10-15%, the mass fraction of dispersant is 1-3%, the mass fraction of calcium lignin sulfonate is 0.3-0.5%, the mass fraction of potassium persulfate is 0.5-1%, and the metal ion concentration is 0.01-0.02mM.

[0019] The mold used to control the thickness of the two layers of hydrogel is composed of two glass plates coated with hydrophobic material and rubber gaskets of different thicknesses, and the thickness of the rubber gasket is between 0.3-1mm.

[0020] In step 3), the crosslinking agent used is N,N′-methylenebisacrylamide, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone dissolved in methanol.

[0021] In step 3), the concentration of N-isopropylacrylamide is 10-20%, the mass of the cross-linking agent is 0.15-2% of N-isopropylacrylamide, the mass fraction of graphene oxide nanoribbons is 0.1-0.5%, the mass of carboxymethyl cellulose is 10-15% of N-isopropylacrylamide, and the mass of 1-hydroxycyclohexyl phenone is 0.5-1% of N-isopropylacrylamide.

[0022] The double-layer hydrogel is responsive to three environmental stimuli: temperature, pH, and near-infrared light. The response to temperature comes from the thermal shrinkage of poly(N-isopropylacrylamide) itself, and the responsiveness to pH comes from the protonation difference of the carboxyl groups in polyacrylic acid and carboxymethyl cellulose. The ability to respond to near-infrared light comes from the combination of the photothermal conversion of graphene oxide nanoribbons and the thermal responsiveness of poly(N-isopropylacrylamide).

[0023] When the double-layer hydrogel is placed under near-infrared light or in water above 32°C, the double-layer hydrogel bends toward the layer containing poly (N-isopropylacrylamide). When the double-layer hydrogel is placed in an acidic solution, the double-layer hydrogel bends toward the layer containing poly (acrylic acid).

[0024] The method is simple and easy to operate. The obtained double-layer hydrogel actuator has good mechanical properties and has good and rapid responsiveness to temperature, pH and near-infrared light. In addition, the polyacrylic acid layer hydrogel also exhibits excellent self-healing properties and strain sensing properties. The triple stimulus responsive double-layer hydrogel actuator has potential applications in the fields of underwater robots, grippers, and valve switches.

[0025] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0026] 1) The present invention introduces graphene oxide nanoribbons into the hydrogel, which not only significantly improves the mechanical properties, self-healing properties and strain sensing properties of the polyacrylic acid hydrogel, but also gives the double-layer hydrogel efficient photothermal conversion ability.

[0027] 2) The double-layer hydrogel actuator prepared by the present invention has triple responsiveness and can respond quickly to temperature, pH and near-infrared light.

[0028] 3) The double-layer hydrogel is prepared by a simple two-step method. The prepared double-layer hydrogel actuator has good mechanical properties and has stable response capabilities to three environmental stimuli. It can be used in soft robots, valve switches and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the response of the double-layer hydrogel actuator under different environmental stimuli. DETAILED DESCRIPTION

[0030] The following specific and detailed operation steps are described below. The following examples are only partial embodiments, not all embodiments. These embodiments are only for illustrating the present invention and are not intended to limit the scope of the present invention.

[0031] Example 1

[0032] Weigh 0.5g of multi-walled carbon nanotubes and disperse them in 150mL of concentrated sulfuric acid. Slowly add 2g of potassium permanganate to it, stir evenly, heat the system to 50°C, react for 1h, and terminate the experiment with ice water containing 5% hydrogen peroxide. After standing at room temperature for 24h, filter and take the upper layer, wash it several times with deionized water, 15% hydrochloric acid solution, ethanol and ether respectively, and obtain graphene oxide nanobelts. Weigh 1.5g of monomer acrylamide, 0.045g of calcium lignin sulfonate, 0.15g of polyvinyl pyrrolidone, 0.075g of potassium persulfate and 1.5mL of monomer acrylic acid in a beaker, and then add 1mL of 1.5mg / mL graphene oxide nanobelt dispersion and 8mL of deionized water. Place the beaker in an ice water bath and stir for 30min, add 1mL of 0.1M iron ion solution to initiate polymerization, stir quickly and evenly, and quickly transfer the pre-gel solution to the mold. Add 1g monomer N-isopropylacrylamide, 0.0015g cross-linking agent N, N'-methylenebisacrylamide and 0.1g carboxymethyl cellulose to another beaker, add 1mL of 1.5mg / mL graphene oxide nanobelt dispersion and 9mL deionized water, stir evenly, add 0.0050g 1-hydroxycyclohexyl phenyl ketone and 100μL methanol premix, place the beaker in an ice water bath and continue stirring for 30min to form a pregel solution, pour the pregel solution on the polyacrylic acid layer and let it stand for 30min, transfer it to ultraviolet light for polymerization, and the thickness of the two layers of hydrogel is controlled by a gasket to be 0.5mm and 0.5mm. Design the hydrogel into a long strip or a cross shape, under near-infrared light irradiation or in deionized water at 40°C, the hydrogel bends toward the poly N-isopropylacrylamide layer, and in an acidic solution of pH=1, the hydrogel bends toward the polyacrylic acid layer.

[0033] Example 2

[0034] Weigh 0.75g of multi-walled carbon nanotubes and disperse them in 180mL of concentrated sulfuric acid. Slowly add 2.2g of potassium permanganate to it. After stirring evenly, heat the system to 55°C. After reacting for 1h, terminate the experiment with ice water containing 20% ​​hydrogen peroxide. After standing at room temperature for 20h, filter and take the upper layer, wash it several times with deionized water, 10% hydrochloric acid solution, ethanol and ether respectively to obtain graphene oxide nanobelts. Weigh 2g of monomer acrylamide, 0.055g of calcium lignin sulfonate, 0.25g of sodium dodecyl sulfate, 0.125g of potassium persulfate and 2mL of monomer acrylic acid in a beaker, and then add 1.5mL of 2mg / mL graphene oxide nanobelt dispersion and 7mL of deionized water. Place the beaker in an ice water bath and stir for 25min. Add 1.2mL of 0.1M silver ion solution to initiate polymerization. After rapid stirring, quickly transfer the pre-gel solution to the mold. Add 1.4g monomer N-isopropylacrylamide, 0.0028g cross-linker N, N'-methylenebisacrylamide and 0.14g carboxymethyl cellulose to another beaker, add 1.5mL of 2mg / mL graphene oxide nanobelt dispersion and 8mL deionized water, stir evenly, add 0.0120g 1-hydroxycyclohexyl phenyl ketone and 90μL methanol premix, place the beaker in an ice water bath and continue stirring for 10min to form a pregel solution, pour the pregel solution on the polyacrylic acid layer and let it stand for 25min, transfer it to ultraviolet light for polymerization, and the thickness of the two layers of hydrogel is controlled by a gasket to be 0.6mm and 0.6mm. Design the hydrogel into a long strip or a cross shape, under near-infrared light irradiation or in 45℃ deionized water, the hydrogel bends toward the poly N-isopropylacrylamide layer, and in an acidic solution of pH=2, the hydrogel bends toward the polyacrylic acid layer.

[0035] Example 3

[0036] Weigh 1g of multi-walled carbon nanotubes and disperse them in 180mL of concentrated sulfuric acid. Slowly add 2.4g of potassium permanganate to it. After stirring evenly, heat the system to 60°C. After reacting for 1h, terminate the experiment with ice water containing 15% hydrogen peroxide. After standing at room temperature for 36h, filter and take the upper layer, wash it several times with deionized water, 25% hydrochloric acid solution, ethanol and ether respectively to obtain graphene oxide nanobelts. Weigh 1.75g ​​of monomer acrylamide, 0.05g of calcium lignin sulfonate, 0.2g of polyvinyl pyrrolidone, 0.1g of potassium persulfate and 1.75mL of monomer acrylic acid in a beaker, and then add 3mL of 1.2mg / mL graphene oxide nanobelt dispersion and 6mL of deionized water. Place the beaker in an ice water bath and stir for 20min. Add 1.5mL of 0.1M iron ion solution to initiate polymerization. After rapid stirring, quickly transfer the pre-gel solution to the mold. Add 1.2g monomer N-isopropylacrylamide, 0.0024g cross-linker N, N'-methylenebisacrylamide and 0.12g carboxymethyl cellulose to another beaker, add 3mL of 1.2mg / mL graphene oxide nanobelt dispersion and 7mL deionized water, stir evenly, add 0.0070g 1-hydroxycyclohexyl phenyl ketone and 105μL methanol premix, place the beaker in an ice water bath and continue stirring for 25min to form a pregel solution, pour the pregel solution on the polyacrylic acid layer and let it stand for 18min, transfer it to ultraviolet light for polymerization, and the thickness of the two layers of hydrogel is controlled by a gasket to 0.6mm and 0.3mm. Design the hydrogel into a long strip or a cross shape, under near-infrared light irradiation or in 55℃ deionized water, the hydrogel bends toward the poly N-isopropylacrylamide layer, and in an acidic solution of pH=5, the hydrogel bends toward the polyacrylic acid layer.

[0037] Example 4

[0038] Weigh 1.25g of multi-walled carbon nanotubes and disperse them in 210mL of concentrated sulfuric acid. Slowly add 2.5g of potassium permanganate to it. After stirring evenly, heat the system to 65°C. After reacting for 1h, terminate the experiment with ice water containing 12% hydrogen peroxide. After standing at room temperature for 30h, filter and take the upper layer, wash it several times with deionized water, 20% hydrochloric acid solution, ethanol and ether respectively to obtain graphene oxide nanobelts. Weigh 2.25g of monomer acrylamide, 0.06g of calcium lignin sulfonate, 0.3g of sodium dodecyl sulfate, 0.15g of potassium persulfate and 2.25mL of monomer acrylic acid in a beaker, and then add 2.5mL of 1.5mg / mL graphene oxide nanobelt dispersion and 5mL of deionized water. Place the beaker in an ice water bath and stir for 15min. Add 1.6mL of 0.1M silver ion solution to initiate polymerization. After rapid stirring, quickly transfer the pre-gel solution to the mold. Add 1.6g monomer N-isopropylacrylamide, 0.0032g cross-linking agent N, N'-methylenebisacrylamide and 0.16g carboxymethyl cellulose to another beaker, add 2.5mL of 1.5mg / mL graphene oxide nanobelt dispersion and 6mL deionized water, stir evenly, add 0.0080g 1-hydroxycyclohexyl phenyl ketone and 95μL methanol premix, place the beaker in an ice water bath and continue stirring for 15min to form a pregel solution, pour the pregel solution on the polyacrylic acid layer and let it stand for 25min, transfer it to ultraviolet light for polymerization, and the thickness of the two layers of hydrogel is controlled by a gasket to be 0.4mm and 0.8mm. Design the hydrogel into a long strip or a cross shape, under near-infrared light irradiation or in 70℃ deionized water, the hydrogel bends toward the poly N-isopropylacrylamide layer, and in an acidic solution of pH=4, the hydrogel bends toward the polyacrylic acid layer.

[0039] Example 5

[0040] Weigh 1.5g of multi-walled carbon nanotubes and disperse them in 250mL of concentrated sulfuric acid. Slowly add 2.7g of potassium permanganate to it. After stirring evenly, heat the system to 50°C. After reacting for 1h, terminate the experiment with ice water containing 10% hydrogen peroxide. After standing at room temperature for 32h, filter and take the upper layer, wash it several times with deionized water, 30% hydrochloric acid solution, ethanol and ether respectively to obtain graphene oxide nanobelts. Weigh 2g of monomer acrylamide, 0.05g of calcium lignin sulfonate, 0.35g of polyvinyl pyrrolidone, 0.125g of potassium persulfate and 2mL of monomer acrylic acid in a beaker, and then add 3mL of 2mg / mL graphene oxide nanobelt dispersion and 4mL of deionized water. Place the beaker in an ice water bath and stir for 30min. Add 2mL of 0.1M iron ion solution to initiate polymerization. After rapid stirring, quickly transfer the pre-gel solution to the mold. Add 1.8g monomer N-isopropylacrylamide, 0.0036g cross-linker N, N'-methylenebisacrylamide and 0.2g carboxymethyl cellulose to another beaker, add 3mL of 2mg / mL graphene oxide nanobelt dispersion and 5mL deionized water, stir evenly, add 0.0090g 1-hydroxycyclohexyl phenyl ketone and 110μL methanol premix, place the beaker in an ice water bath and continue stirring for 20min to form a pregel solution, pour the pregel solution on the polyacrylic acid layer and let it stand for 15min, transfer it to ultraviolet light for polymerization, and the thickness of the two layers of hydrogel is controlled by a gasket to be 0.6mm and 0.8mm. Design the hydrogel into a long strip or a cross shape, under near-infrared light irradiation or in deionized water at 65°C, the hydrogel bends toward the poly N-isopropylacrylamide layer, and in an acidic solution of pH = 4.5, the hydrogel bends toward the polyacrylic acid layer.

[0041] Example 6

[0042] Weigh 1g of multi-walled carbon nanotubes and disperse them in 200mL of concentrated sulfuric acid. Slowly add 2.5g of potassium permanganate to it. After stirring evenly, heat the system to 65°C. After reacting for 1h, terminate the experiment with ice water containing 15% hydrogen peroxide. After standing at room temperature for 28h, filter and take the upper layer, wash it several times with deionized water, 20% hydrochloric acid solution, ethanol and ether respectively to obtain graphene oxide nanobelts. Weigh 1.8g of monomer acrylamide, 0.055g of calcium lignin sulfonate, 0.45g of sodium dodecyl sulfate, 0.125g of potassium persulfate and 1.8mL of monomer acrylic acid in a beaker, and then add 1.5mL of 2.5mg / mL graphene oxide nanobelt dispersion and 8mL of deionized water. Place the beaker in an ice water bath and stir for 25min. Add 1.5mL of 0.1M silver ion solution to initiate polymerization. After rapid stirring, quickly transfer the pre-gel solution to the mold. Add 2g monomer N-isopropylacrylamide, 0.004g cross-linker N, N'-methylenebisacrylamide and 0.18g carboxymethyl cellulose to another beaker, add 1.5mL of 2.5mg / mL graphene oxide nanobelt dispersion and 7mL deionized water, stir evenly, add 0.0080g 1-hydroxycyclohexyl phenyl ketone and 90μL methanol premix, place the beaker in an ice water bath and continue stirring for 25min to form a pregel solution, pour the pregel solution on the polyacrylic acid layer and let it stand for 30min, transfer it to ultraviolet light for polymerization, and the thickness of the two layers of hydrogel is controlled by a gasket to be 0.5mm and 1mm. Design the hydrogel into a long strip or a cross shape. Under near-infrared light irradiation or in deionized water at 60℃, the hydrogel bends toward the poly N-isopropylacrylamide layer, and in an acidic solution of pH=3, the hydrogel bends toward the polyacrylic acid layer.

Claims

1. A method for preparing a triple stimulus responsive double-layer hydrogel actuator, characterized in that: Here are the steps: 1) dispersing a certain amount of multi-walled carbon nanotubes in concentrated sulfuric acid, slowly adding potassium permanganate thereto, stirring evenly under magnetic stirring, raising the system to a certain temperature and continuing stirring, adding ice water containing hydrogen peroxide to terminate the reaction, separating the product after standing, and then washing it several times with deionized water, hydrochloric acid solution, ethanol and ether in sequence to obtain graphene oxide nanoribbons; 2) adding different amounts of two monomers, acrylic acid and acrylamide, a dispersant, calcium lignin sulfonate, potassium persulfate and the graphene oxide nanoribbons prepared in step 1) into a beaker and stirring evenly with water, adding a metal ion solution under ice water bath conditions, stirring vigorously for a short time and pouring into a mold for polymerization, and controlling the thickness of this layer of hydrogel; wherein the metal ion is selected from iron ions or silver ions; 3) placing N-isopropylacrylamide, a crosslinking agent, the graphene oxide nanoribbons prepared in step 1) and carboxymethyl cellulose in deionized water and stirring, adding a certain amount of photoinitiator and stirring for a certain period of time in an ice water bath, pouring the obtained pre-gel solution on the polyacrylic acid-polyacrylamide layer prepared in step 2), leaving it for a period of time, and then photoinitiating polymerization under ultraviolet light to obtain a double-layer hydrogel; 4) The double-layer hydrogel is cut into strips, and the strip hydrogel bends toward the layer containing poly (N-isopropylacrylamide) under near-infrared light or in a hot water environment. When the bent strip hydrogel is placed in an acidic solution, the double-layer hydrogel bends toward the layer containing polyacrylic acid.

2. The method for preparing the triple stimulus responsive double-layer hydrogel actuator according to claim 1, characterized in that: In step 1), the mass of the multi-walled carbon nanotubes is 0.5-1.5 g, the volume of concentrated sulfuric acid is 150-250 mL, the mass of potassium permanganate is 2-3 g, the mixed solution is heated to 55-60° C., the concentration of hydrogen peroxide ice water is 5-20%, and the concentration of hydrochloric acid solution is 10-30%.

3. The method for preparing the triple stimulus responsive double-layer hydrogel actuator according to claim 1, characterized in that: In step 2), the dispersant used is selected from polyvinyl pyrrolidone or sodium lauryl sulfate.

4. The method for preparing a triple stimulus responsive double-layer hydrogel actuator according to claim 1, characterized in that: In step 2), the mass fraction of graphene oxide nanoribbons is 0.1-0.5%, the mass fraction of acrylic acid and acrylamide monomers is 10-15%, the mass fraction of dispersant is 1-3%, the mass fraction of calcium lignin sulfonate is 0.3-0.5%, the mass fraction of potassium persulfate is 0.5-1%, and the metal ion concentration is 0.1 mol / L.

5. The method for preparing a triple stimulus responsive double-layer hydrogel actuator according to claim 1, characterized in that: The mold used to control the thickness of the two layers of hydrogel is composed of two glass plates coated with hydrophobic material and rubber gaskets of different thicknesses, and the thickness of the rubber gasket is between 0.3-1mm.

6. The method for preparing a triple stimulus responsive double-layer hydrogel actuator according to claim 1, characterized in that: In step 3), the crosslinking agent used is N,N′-methylenebisacrylamide, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone dissolved in methanol.

7. The method for preparing a triple stimulus responsive double-layer hydrogel actuator according to claim 6, characterized in that: In step 3), the concentration of N-isopropylacrylamide is 5-8%, the mass of the cross-linking agent is 0.15-2% of N-isopropylacrylamide, the mass fraction of graphene oxide nanoribbons is 0.1-0.5%, the mass of carboxymethyl cellulose is 10-15% of N-isopropylacrylamide, and the mass of 1-hydroxycyclohexyl phenone is 0.5-1% of N-isopropylacrylamide.

8. The method for preparing a triple stimulus responsive double-layer hydrogel actuator according to claim 1, characterized in that: When the double-layer hydrogel is placed under near-infrared light or in water above 32°C, the double-layer hydrogel bends toward the layer containing poly (N-isopropylacrylamide); when the double-layer hydrogel is placed in an acidic solution, the double-layer hydrogel bends toward the layer containing polyacrylic acid.

9. A triple stimulus responsive double-layer hydrogel actuator prepared according to the preparation method according to any one of claims 1 to 8, wherein the triple stimulus responsive double-layer hydrogel is responsive to temperature, pH and near-infrared light.

Citation Information

Patent Citations

  • Graphene nanobelt-polyaniline nanobelt composite material and preparation method thereof

    CN108570229A

  • Hydrogel driver containing nanometer microspheres, and preparation method and application of hydrogel driver

    CN111909304A